MACHKA - BUSINESS PLAN: A gastronomic experience that will transport you to Ecuador - Cevallos, Paul (2017)
The present work is a business plan of a new restaurant called "Machka", which offers a concept of Ecuadorian cuisine in a casual and relaxed atmosphere. One important aspect of the business is the use of technology to engage its consumers throughout social media, restaurant official website, and a mobile application. Indeed, the business plan shows what the founders want to achieve and how they plan to get there, including a deep analysis of strategy, objectives, operating and commercial plans, risk assessment, and financial projections.